2020
DOI: 10.1002/jmv.26746
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syndrome coronavirus‐2 response: Microbiota as lactobacilli could make the difference

Abstract: Coronavirus disease 2019 (COVID‐19) is caused by respiratory syndrome coronavirus qualified as SARS‐CoV‐2. Viral penetration requires binding of the viral spike (S) protein to a specific cellular receptor (ACE2) highly expressed in a nasal goblet and ciliated cells. In several countries, the COVID‐19 evolution was relatively benign compared to others and despite noncompliance with health recommendations on several occasions. In this overview, we attempt to define the criteria that could explain such a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…Probiotics are known to secrete beneficial metabolites termed as postbiotics which could promote immunomodulatory effects and antibacterial and antiviral mechanisms; thus, it is unsurprising that probiotics were advocated as potential adjuvant therapy or prevention against SARS-COV-2 infection [28][29][30][31][32][33]. Some postbiotics, including bacteriocins have been proven to migrate across human epithelial cells to exert therapeutic effects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are known to secrete beneficial metabolites termed as postbiotics which could promote immunomodulatory effects and antibacterial and antiviral mechanisms; thus, it is unsurprising that probiotics were advocated as potential adjuvant therapy or prevention against SARS-COV-2 infection [28][29][30][31][32][33]. Some postbiotics, including bacteriocins have been proven to migrate across human epithelial cells to exert therapeutic effects [34].…”
Section: Discussionmentioning
confidence: 99%
“…17 In the context of SARS-CoV-2 infection, lactobacilli may act as a barrier to viral penetration through several mechanisms. 38 Lactobacillus gasseri Kx110A1 was reported to attenuate SARS-CoV-2 infection by inhibiting the expression of a disintegrin and metalloprotease 17 (ADAM 17), 39 an enzyme that participates in ACE2 ectodomain shedding and that has been shown to play a role in the entry of SARS-CoV, since ADAM17 silencing was found to reduce SARS-CoV infection. 40 Moreover, a computational study found that plantaricin, a bacteriocin secreted by Lactiplantibacillus plantarum, may possess SARS-CoV-2 antiviral activity by interacting with the receptor-binding domain (RBD) of the viral spike glycoprotein and thus blocking SARS-CoV-2 cellular entry.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculate that increases in gut Lactobacillus numbers may therefore be a host adaptive host response to viral infection. Administration of Lactobacillus strains in mice can decrease asthmatic symptoms (46)(47)(48)(49), decrease airway inflammation and alveolar damage (49,50), and provide protection against respiratory viral infection (23,45,51). Thus, we might expect Lactobacillus numbers to increase in those animals with chronic FURTD signs compared to controls as an adaptive response.…”
Section: Discussionmentioning
confidence: 99%